Immunohistochemical study of bone marrow angiogenesis using CD34 in adult acute lymphoblastic leukemia and its correlation with various pathological, laboratory and clinical parameters - Moulod, Sarab H.; Jaafar, Abdulkareem M.; Alkhafajy, Ali H. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: In recent years, bone marrow angiogenesis is indicated to be involved in the pathogenesis and progression of certain hematological malignancies like acute leukemia, lymphomas, and multiple myeloma. Recent studies have suggested that bone marrow angiogenesis plays an important role in the pathogenesis of adult acute lymphoblastic leukemia and also has prognostic value in the disease.Objectives: at the present study, bone marrow angiogenesis in ALL will be examined using immunohistochemical staining for CD34, and this will be correlated with various pathological, laboratory and clinical parameters.Patients and methods: A retrospective cross-sectional study was done on 60 patients with acute lymphoblastic leukemia (32 males & 28 females) compared with 20 controls (anemic patients), all recruited at the Medical City Hospital/ Teaching Laboratories/ Baghdad from January 2010 to December 2012. The bone marrow biopsy of each was re-examined histologically. BM angiogenesis was studied by immunohistochemical staining for CD34 to identify microvessels.Results: The bone marrow microvessel density was markedly and significantly increased in patients with acute lymphoblastic leukemia compared with bone marrow controls (p = 0.0001). There was a significant association between angiogenesis grade III and WBC count more than 30×109/L (P > 0.0001).Conclusions: Angiogenesis in ALL was significantly higher than control group. Increase angiogenesis confirmed by IHC was significantly correlated with high WBC at diagnosis. These observations suggest that the combination of anti antiangiogenic therapy might apply to leukemia.